2016
DOI: 10.1021/acs.est.6b00825
|View full text |Cite
|
Sign up to set email alerts
|

Modulation in Persistent Organic Pollutant Concentration and Profile by Prey Availability and Reproductive Status in Southern Resident Killer Whale Scat Samples

Abstract: Persistent organic pollutants (POPs), specifically PCBs, PBDEs, and DDTs, in the marine environment are well documented, however accumulation and mobilization patterns at the top of the food-web are poorly understood. This study broadens the understanding of POPs in the endangered Southern Resident killer whale population by addressing modulation by prey availability and reproductive status, along with endocrine disrupting effects. A total of 140 killer whale scat samples collected from 54 unique whales across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 65 publications
3
20
0
Order By: Relevance
“…Lundin et al [8,50] showed that POPs, namely PCBs, DDTs, and PBDEs, increase in circulation in SRKWs when Fraser River Chinook abundance is lowest, presumably due to increased fat metabolism in response to nutritional stress. Mobilization of contaminants into circulation also occurs during the energetic demands of lactation, with an estimated 70–90% lactation transfer of maternal toxicant burden in primiparous females [51].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lundin et al [8,50] showed that POPs, namely PCBs, DDTs, and PBDEs, increase in circulation in SRKWs when Fraser River Chinook abundance is lowest, presumably due to increased fat metabolism in response to nutritional stress. Mobilization of contaminants into circulation also occurs during the energetic demands of lactation, with an estimated 70–90% lactation transfer of maternal toxicant burden in primiparous females [51].…”
Section: Discussionmentioning
confidence: 99%
“…High POP burden has specifically been associated with disruption of reproduction success and reduced calf survival in marine mammals [5255]. Most notably, Lundin et al [8] found increased Persistent PCBs, the group of PCBs considered more persistent and more toxic [56], in the female whales classified with UPg’s (73%; 95% CI, 61–85) compared to all other female reproductive groups (range 43–56%). Further evidence in support of the occurrence of UPg in this population is the unexpected inverse in bioaccumulation of POPs with age in “nulliparous” mature females (3 of 4 nulliparous whales had an unsuccessful pregnancy defined by fecal hormone measures).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced abundance of their primary prey, Chinook salmon ( Oncorhynchus tshawytscha ), during warming ocean episodes has coincided with subsequent periods of higher mortality in resident killer whale populations (Ford et al., ). As PCBs are fat‐soluble contaminants that amplify in food webs, productivity‐related reduction in lipids may concentrate PCBs in the diminishing blubber stores of marine mammals (Jenssen et al., ; Lundin et al., ; McKinney et al., ; Ross et al., ). While pollution risks by PCBs, noise and disturbance, and reduce prey abundance (i.e., Chinook salmon) are known to affect these killer whales (Alava et al., ; Cullon et al., ; Ford et al., ; Hickie et al., ; Lundin et al., ; Ross et al., ), the combined impact of climate change and PCBs on this top predator and its prey is poorly understood.…”
Section: Case Study: Climate–pollutant Impacts On Apex Predators In Tmentioning
confidence: 99%